Increasing role of abstinence and infecundity in non-use of contraceptive methods in India. Issue 2 (9th March 2021) - Dhillon, Preeti; Singh, Govind; Ram, Faujdar; Kumar, Pradeep; Saggurti, Niranjan
Abstract: This paper assesses the reasons for non-use of contraceptive methods, and the possible complexity of reported data on women in India. The study used recent data from two successive rounds of the National Family Health Survey (NFHS) (2005–06: N =37, 296; 2015–16: N =247, 024), which surveyed currently married women aged 15–49 years. The reporting on non-use of contraceptives and the changing pattern of the reasons for non-use were analysed, classified into fertility and other cited reasons. The self-reported reasons for non-use of contraception were verified with other related information captured in the survey. Bivariate and logistic regression analyses were conducted. Sexual abstinence (not having sex: 10%; infrequent sex: 3%) and infecundity (menopausal/hysterectomy: 12%; subfecund/infecund: 10%) were the most commonly reported reasons for non-use of contraceptive methods in 2015–16, followed by refusal to use (10%). The proportion of non-users who wanted to have a child soon (25% to 21%), were pregnant (16% to 13%), in postpartum amenorrhoea (68% to 40%) and who had method-related reasons (10% to 6%) declined over time (from 2005–06 to 2015–16, respectively). A higher proportion of less-educated women reported abstinence (6%) and menopause/hysterectomy (19%) than educated women. Abstinence was more commonly reported in states with low prevalence of modern contraceptive use. The findings suggest that the increasing trend of abstinence and infecundity among non-users of contraception may be a concern for future research and reproductive health programmes, as it questions both the quality of data and sexual health of married couples.